A dual‐band half‐mode substrate integrated waveguide‐based antenna for WLAN/WBAN applications. Issue 5 (24th January 2018) - Chaturvedi, Divya; Raghavan, S.
Abstract: A dual‐band half‐mode substrate integrated waveguide (HMSIW) based cavity‐backed antenna is proposed for WLAN/WBAN applications at 5/5.8 GHz, respectively. A semi‐hexagonal slot is introduced on the top plane of the cavity primarily for radiation. This slot offers miniaturization for both the TM210 and TM020 modes. Later on, two rectangular slits are loaded on the open edge of the patch, to provide miniaturization and tuning mainly for the higher frequency band. The performance of the proposed antenna is investigated in free space and in proximity of the pork tissues. In free space conditions, the measured −10 dB fractional bandwidths are 3% and 3.1% along with peak gains of 6.25 and 6 dBi for the frequency bands at 5 and 5.8 GHz, respectively. In proximity of the pork tissues, the measured fractional bandwidth is 3.2% along with the efficiency of 81.5% at 5.8 GHz. The specific absorption rate (SAR) is 0.48 mW/g averaged over 1 g of tissues with 100 mW input power.